Inovasi Model Pembelajaran Pai Menggunakan Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa di Smpn 1 Purwosari - Mutmainah; Muhammad Nur Hadi; M. Anang Solikhudin; Muhammada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Acquiring knowledge Islamic Religious Education is a methodical endeavor to develop into a strong person capable of putting Islamic teachings into practice in daily life in order to reach human perfection. The goal of the learning process is to help each student reach their full potential and become as capable as possible. In the classroom, an instructor's or teacher's function is identical to that of a mentor and motivator who supports students' growth. Determining learning outcomes and student engagement when utilizing manual and audio-visual media is the aim of this study. Here, qualitative research methodologies are employed by the researchers, and the goal of the learning process is to maximize each student's potential. In a classroom setting, an instructor or teacher plays the same function as a mentor and motivator who